JENIS DAN KARAKTERISTIK DATA PENDIDIKAN ISLAM - Norlaila; Ladia; Dina Hermina (Jurnal Riset Multidisiplin Edukasi, 2026)
Islamic education data plays a central role in supporting the successful governance of Islamic educational institutions. Through data, every educational activity can be systematically recorded, from planning and implementation to evaluation. This study examines the types and characteristics of Islamic education data, encompassing four main aspects: academic data, administrative data, financial data, and religious data. The method used is a literature review, reviewing various scientific sources on Islamic education data and information management. The study results indicate that accurate, valid, and integrated data management is essential for effective and efficient decision-making in Islamic educational institutions. Furthermore, the use of information technology in data management facilitates the recording, processing, and presentation of information quickly and transparently. In conclusion, Islamic education data serves not only as an administrative tool but also as a strategic instrument in realizing superior, competitive education quality rooted in Islamic values.